2006
DOI: 10.1161/01.hyp.0000197613.47649.02
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Neural Outflow and Chemoreflex Sensitivity Are Related to Spontaneous Breathing Rate in Normal Men

Abstract: Abstract-Respiration contributes importantly to short-term modulation of sympathetic nerve activity. However, the relationship between spontaneous breathing rate, chemoreflex function, and direct measures of sympathetic traffic in healthy humans has not been studied previously. We tested the hypothesis that muscle sympathetic nerve activity and chemoreflex sensitivity are linked independently to respiratory rate in normal subjects. We studied 69 normal male subjects aged 29.6Ϯ8.1 years. Subjects were subdivide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 35 publications
5
50
0
2
Order By: Relevance
“…It is worthwhile to mention that recent reports show that reduced overall HRV and increased LF spectral power are associated with increased mortality (53), hypertension (36), and sympathetic overactivity (12,36). Moreover, studies performed in humans with OSA detected an increased peripheral chemoreflex drive (31,32) and reduced HRV with LF predominance (29). Interestingly, Narkiewicz et al (29) reported that patients with mild OSA presented decreased overall HRV without changes in BPV, while patients with moderate to severe OSA showed increased BPV.…”
Section: Discussionmentioning
confidence: 92%
“…It is worthwhile to mention that recent reports show that reduced overall HRV and increased LF spectral power are associated with increased mortality (53), hypertension (36), and sympathetic overactivity (12,36). Moreover, studies performed in humans with OSA detected an increased peripheral chemoreflex drive (31,32) and reduced HRV with LF predominance (29). Interestingly, Narkiewicz et al (29) reported that patients with mild OSA presented decreased overall HRV without changes in BPV, while patients with moderate to severe OSA showed increased BPV.…”
Section: Discussionmentioning
confidence: 92%
“…One of the hypotheses raised would be the reduction of nervous sympathetic activity: reductions in respiratory frequency of about 6 to 10 breaths per minute, as they increase tidal volume, would stimulate cardiopulmonary stretch receptors, which conversely would reduce the discharge of efferent sympathetic fibers, resulting in decreased systemic vascular resistance and consequent reduction of arterial pressure. 9 However, such a hypothesis has not yet been fully confirmed in hypertensive patients who regularly perform this type of intervention. …”
Section: To the Editormentioning
confidence: 99%
“…The change in RR intervals caused by breathing is known as respiratory sinus arrhythmia, which is regulated by breathing phase, depth, and rate [14][15][16]. The variation of RR intervals with respiration was suggested as a measure of the autonomic nervous system function in the 1970s, and it has been evaluated by different methods with particular focus on the spectral approach to HRV, but never with an analysis of Poincaré plots [14,[17][18][19] …”
mentioning
confidence: 99%